The most frequent diagnosis on patients undergoing hemodialysis - Nurjannah, Intansari; Mailani, Fitri (International Journal of Research in Medical Sciences, 2016)
Background: Hemodialysis is a routine medical intervention for patient with chronic renal failure. Patients may responds differently when they undergoing this procedure. Investigating nursing diagnosis and collaborative diagnoses during hemodialysis procedure need to be explored. The objective of this research is to determine the sequence of nursing diagnosis and the collaborative diagnosis identified among kidney disease patients who are undergoing hemodialysis. Methods: This case study research involving 62 respondents. Research was conducted between June and July 2015. The respondents’ cases were studied to determine what nursing diagnoses and collaborative diagnoses, using a six-step diagnostic reasoning method. Results: Result of this study showed 27 nursing diagnoses and 7 collaborative diagnoses experienced by the patients. The six most commonly experienced nursing diagnoses were: activity intolerance (100%), nausea (96.8%), risk for impaired skin integrity (91.9%), impaired urinary elimination (82.3%), insomnia (77.4%), and sexual dysfunction (58.1%). Conclusions: There were 27 nursing diagnoses and 7 collaborative diagnoses that were experienced by patients who were undergoing hemodialysis.